Case Study - Pumpable Emulsion Trials in Tunneling and Stoping - Eduardo Berger (International Society of Explosives Engineers, 1991)
This paper describes a mechanized loading system, the HYDRODOSE, which allows the use of pumpable emulsions in underground mining. It also describes a pumpable emulsion explosive for small diameter holes, HYDROMITE PDB. Included are test results carried out in two Chilean underground mines.